Influences on the work engagement of secondary school teachers in rural Kwazulu-Natal - Gunram Dehaloo; Salomé Schulze (The Journal for Transdisciplinary Research in Southern Africa, 2013)
The aim of this research was to investigate the influence of job resources and job demands on the work engagement of secondary school teachers in the Illembe district of KwaZulu-Natal. A previously developed model for work engagement was used as conceptual framework. In the empirical investigation the authors used a mixed-method, explanatory research design. In the quantitative phase 100 teachers from five schools completed a self-constructed questionnaire which allowed for hypotheses testing. This was followed by 16 interviews with teachers from the same sample. The study revealed that the teachers exhibited low levels of work engagement. This was related to inadequate job resources and excessive job demands. The teachers were particularly displeased with their remuneration packages. However, teachers of different genders, cultures, levels of experience and educational qualifications differed in their perceptions. Through the interview data the authors gained a deeper understanding of how the above-mentioned impacted on work engagement. The study is significant for illuminating current factors that managers should consider to improve the work engagement of teachers.